Neo-mechanistic explanatory integration for cognitive science: the problem of reduction remains - Leite, Diego Azevedo (Sofia, 2019)
One of the central aims of the neo-mechanistic framework for the neural and cognitive sciences is to construct a pluralistic integration of scientific explanations, allowing for a weak explanatory autonomy of higher-level sciences, such as cognitive science. This integration involves understanding human cognition as information processing occurring in multi-level human neuro-cognitive mechanisms, explained by multi-level neuro-cognitive models. Strong explanatory neuro-cognitive reduction, however, poses a significant challenge to this pluralist ambition and the weak autonomy of cognitive science derived therefrom. Based on research in current molecular and cellular neuroscience, the framework holds that the best strategy for integrating human neuro-cognitive theories is through direct reductive explanations based on molecular and cellular neural processes. It is my aim to investigate whether the neo-mechanistic framework can meet the challenge. I argue that leading neo-mechanists offer some significant replies; however, they are not able yet to completely remove strong explanatory reductionism from their own framework.